Solusi Pendidikan Berkelanjutan Untuk Menanggulangi Brain Rot Pada Siswa - Faizal Rahman, Iqbal (Jurnal Syntax Fusion, 2025)
Sustainable education plays a crucial role in creating a healthy learning environment, especially in the ever-evolving digital era. Brain rot, or the decline in cognitive abilities due to uncontrolled exposure to technology, has become one of the main challenges in modern education. The solution to sustainable education in this context focuses on balancing the use of technology with the enhancement of critical thinking and healthy learning habits. With a more humanistic approach and educational technology that fosters growth, sustainable education can effectively address brain rot. This study analyzes ways to integrate curricula that prioritize the development of students' emotional and social intelligence, while also recommending training programs for educators to better understand the negative impacts of digitalization on children's cognitive development. Ultimately, the proposed solution aims to create a generation that is more adaptive to the changing times without losing the depth and meaning of their learning.